The Patronage Behaviour of Islamic Bank’s Customers: Empirical Studies in Aceh - M. Shabri Abd. Majid; Said Zulhanizar (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This study is aimed at empirically exploring the pertinent factors, which customers and non-customer perceive as germane to their selection of Islamic bank in Aceh, Indonesia. A sample of 300 customers and non-customer of Bank Aceh Syariah were selected based on the convenience sampling technique. Using the logistic regression technique, the study documented that the customers’ selection of the banks were influenced by the factors of banks’ characteristic, services and trust, shari’ah compliance, and physical objects. Of these factors, banks’ characteristic and shari’ah compliance were found to be the most pertinent factors perceived by the customers and non-customer to their selection of Islamic bank in Aceh, Indonesia. These findings imply that to attract more customers, the Islamic bank should enhance their unique characteristics and products’ compliance.DOI:10.15408/aiq.v8i2.3139